Superconductivity with high hardness in Mo3C2. Issue 5 (12th April 2019) - Ge, Yufei; Ma, Shuailing; Bao, Kuo; Tao, Qiang; Zhao, Xingbin; Feng, Xiaokang; Li, Li; Liu, Bo; Zhu, Pinwen; Cui, Tian
Abstract : This work synthesized a high hardness and superconductive polycrystalline Mo3 C2 material by the HPHT method. Mo3 C2 exhibits superconductivity below 8.2 K and its hardness is far higher than that of the traditionally used superconductive materials. Abstract : Inserting light element atoms into a transition metal host matrix simultaneously produces high hardness and high superconductivity transition temperature. Here, we report the synthesis of a polycrystalline 'covalent metal' – Mo3 C2 (with space group: P 63/ mmc ) with the high pressure and high temperature (HPHT) method. Direct magnetic susceptibility and electrical resistivity measurements show that Mo3 C2 is a typical weakly coupled type-II superconductor with a high critical magnetic field and a superconductive temperature of 8.2 K. Moreover, compared with traditional superconductive materials, the asymptotic Vickers hardness value of Mo3 C2 shows impressive high hardness. Its high superconductive temperature originates from its high Debye temperature and high density of states at the Fermi energy level. The high Debye temperature is closely correlated with the hybridization between Mo-4d orbitals and C-2p orbitals, and the metallic feature leads to the high density of states at the Fermi energy level N (EF ). The advent of this class of high hardness superconductive materials bridges the gap between high hardness and superconductivity communities.